Reestablecimiento de imágenes renderizadas afectadas por ruido blanco gaussiano aditivo, ruido sal y pimienta y distorsión geometrica espacial con problemas de rotación y movimiento vertical, mediante la herramienta matlab - Almachi González., Julio César (2010)
This report makes a study of factors affecting software rendered images of architectural and graphic design as Autocad, Adobe Photoshop, Arcon 6.5, the image processing is based on adding noise and distortion to the same geometric space for later using direct algorithms and filters to be removed, use the standardized root mean square error estimator quality as compared with the original image is processed. In the first chapter a general reference of terms and definitions used throughout the project in order to have clear concepts and to develop the idea of this work. The second chapter provides an explanation of how they work and the application to have the algorithms to remove noise from images outlining the advantages, it also explains what spatial geometric distortion with rotational problems and vertical movement as well as and elimination. In the final chapter explains the development of the tool, the inconvenience that arose in their design and the solutions were found. Is added to the user manual and the code of the original program.